Designing Phantom Femur Using Gypsum Material as an Alternative to Human Bone in the Radiology Department of Simpang Lima Gumul Hospital Kediri - Vike Meidina; Yuniar Alam; Ulfa Niswatul Khasanah (BULETIN FISIKA, 2026)
The purpose of this study was to evaluate the similarity of radiation characteristics between femur phantoms and human bones. A total of six samples were used, made of gypsum composed of calcium sulfate hemihydrate (CaSO4•1/2H2O). The femur phantoms used were ± 2.5 cm long with a diameter of 14 cm. The cassette used measured 30x40cm. Based on the test results at Simpang Lima Gumul Regional General Hospital, the Hounsfield Unit (HU) value of the phantom was 1084.74 HU, and the Hounsfield Unit (HU) value of real bone was 1598.8 HU, with a difference of 32.15%. The HU value of the bone in axial scanning ranged from +800.15 HU to +1112.03 HU, and in helical scanning ranged from +852.57 HU to +1188.28 HU, with a tolerance range between +700 HU and +3000 HU. The femur phantom fabricated from gypsum demonstrated an average Hounsfield Unit value of 1084.74 HU, falling within the tolerance range of natural bone (700–3000 HU), thereby resembling the radiological density of bone.